Polymorphic nuclear markers for coastal plant species with dynamic geographic distributions, the rock samphire (Crithmum maritimum) and the vulnerable dune pansy (Viola tricolor subsp. curtisii) - Latron, Mathilde; Arnaud, Jean-François; Ferla, Héloïse; Godé, Cécile; Duputié, Anne (Molecular biology reports, 2018)
Identifying spatial patterns of genetic differentiation across a species range is critical to set up conservation and restoration decision-making. This is especially timely, since global change triggers shifts in species’ geographic distribution and in the geographical variation of mating system and patterns of genetic differentiation, with varying consequences at the trailing and leading edges of a species’ distribution. Using 454 pyrosequencing, we developed nuclear microsatellite loci for two plant species showing a strictly coastal geographical distribution and contrasting range dynamics: the expanding rock samphire ( Crithmum maritimum , 21 loci) and the highly endangered and receding dune pansy ( Viola tricolor subsp. curtisii , 12 loci). Population genetic structure was then assessed by genotyping more than 100 individuals from four populations of each of the two target species. Rock samphire displayed high levels of genetic differentiation ( F ST = 0.38), and a genetic structure typical of a mostly selfing species ( F IS ranging from 0.16 to 0.58). Populations of dune pansy showed a less pronounced level of population structuring ( F ST = 0.25) and a genotypic structure more suggestive of a mixed-mating system when excluding two loci with heterozygote excess. These results demonstrate that the genetic markers developed here are useful to assess the mating system of populations of these two species. They will be tools of choice to investigate phylogeographical patterns and variation in mating system over the geographical distribution ranges for two coastal plant species that are subject to dynamic evolution due to rapid contemporary global change.